Slask, wojna, Kresy, Wroclaw, Nowa Huta : wspomnienia 1930-1960 - Binek, Tadeusz (Krakow : Oficyna Cracovia, 1997)
Autobiographical memoirs of a Polish settler from Silesia in the years 1930 to 1960.
Errata slip inserted.
Keywords: Binek, Tadeusz; Silesia -- Biography; Silesia -- History -- 20th century; Poland -- Biography